The quality of life and related factors in older adults with possible sarcopenia and sarcopenia in rural areas of Xinjiang, China: a cross sectional study - Yajie Che; Huiling Xia; Nan Zhang; Shan Yu; Kaiyang Guo; Yan Tang; Mei Sun; Ping Yan (BMC Geriatrics)
Abstract Background Studies have shown that sarcopenia prevalence in the Chinese population aged over 60 years was 14%. The quality of life of older adults with sarcopenia has drawn increasing attention. Sarcopenia-related quality of life has not been well studied. We explored the quality of life of patients with sarcopenia and the related influencing factors in Xinjiang. Methods This study was conducted from July–September 2023 in the northern and southern regions of Xinjiang, China. Possible sarcopenia and sarcopenia were diagnosed according to the AWGS 2019. The Sarqol® questionnaire was used to evaluate quality of life. A linear regression model with a stepwise method was used to identify quality-of-life-associated factors for possible sarcopenia and sarcopenia. Results A total of 987 older adults were enrolled,18.5% had possible sarcopenia, and 15.1% had sarcopenia. Quality of life scores: possible sarcopenia 26.46–92.55 (56.31 ± 14.69), sarcopenia 30.74–90.93 (56.91 ± 13.45).The indicators for which the difference analysis were meaningful, in the group with possible sarcopenia are gender, inhabiting information, ACCI score, hearing loss, social support level and self-rated risk of falling. In the sarcopenia group are gender, ACCI score, hearing loss, vision loss, self-rated health status, number of remaining teeth, self-rated risk for falling, and dysphagia status. The risk factors for quality of life in patients with possible sarcopenia were gender and hearing loss, whereas self-rated of general health, self-rated of poor health, self-rated of very poor health and falls were risk factors in the sarcopenia group. Conclusion This study focused on quality of life and factors in older adults with possible sarcopenia or sarcopenia. The research results showed that in order to prevent the decline in the quality of life of older adults with sarcopenia, it is very important to regularly examine the oral health status of the older adults, prevent the occurrence of chronic diseases.Multimodal interventions address common sensory impairments.Carry out aging-friendly renovation of the home environment and conduct balance training to prevent the occurrence of falls among the older adults.